A 3-Year Follow-Up and Radiological Analysis of Cochlear Implantation Patients with Cochlear Nerve Deficiency and Modiolar Deficiency-Type Malformations. Issue 1 (17th January 2023) - Lu, Simeng; Wei, Xingmei; Kong, Ying; Chen, Biao; Chen, Jingyuan; Zhang, Lifang; Yang, Mengge; Xue, Shujin; Shi, Ying; Liu, Sha; Xu, Tianqiu; Dong, Ruijuan; et al.
Abstract : Objective: Cochlear nerve deficiency (CND) is often combined with modiolar deficiency-type inner ear malformations, which cause variable cochlear implantation (CI) outcomes. We aimed to assess the postoperative development of auditory and speech perception in CND patients with modiolar deficiency-type malformations after 3 years of follow-up to determine the factors correlated with CI outcomes. Methods: Sixty-seven CND patients with modiolar deficiency-type malformations who underwent CI surgery were retrospectively reviewed. Modiolar deficiency-type malformations included common cavity (CC), cochlear hypoplasia (CH) (including CH-I and CH-II) and incomplete partition-I (IP-I). Categorical auditory performance (CAP) and the infant-toddler meaningful auditory integration scale (MAIS) were used to assess auditory ability. The speech intelligibility rating (SIR) and meaningful use of speech scale (MUSS) were used to assess the speech intelligibility of these CI patients. The CI outcomes were evaluated at 0, 12, 24 and 36 months after implant activation. Results: All patients demonstrated improvements in auditory ability and speech intelligibility after CI. There were no significant differences in CI outcomes at any time point according to the malformation type. The number of nerve bundles within the internal auditory canal (IAC) showed significant differences at 12, 24 and 36 months after CI ( p < 0.05). Patients with one nerve bundle had relatively poor CI outcomes. Conclusions: CND patients with modiolar deficiency-type malformations showed continuous improvement in auditory and speech abilities after CI. Compared with malformations, the number of nerve bundles should be given more attention when selecting the side for CI.